Psychometric Reliability to Assess the Perception of Women's Fulfillment of Maternity Rights - Claudia Susana Silva-Fernández; María de la Calle; Paul Anthony Camacho; Silvia M. Arribas; Eva Garrosa; David Ramiro-Cortijo (MDPI AG, 2024)
The fulfillment of rights to maternal healthcare is a key factor for the wellbeing of women. However, there is a lack of an instrument to ascertain the experience of women during maternity to enable adequate monitoring. The aim of this study was to validate a new instrument to measure women's perception of the fulfillment of rights during healthcare in pregnancy and childbirth and immediately postpartum. The initial version of the instrument consists of 50 items and was validated using exploratory factor analysis. Additionally, the final version of the instrument consists of 29 items and was validated by confirmatory factor analysis and known-group validity. The instrument was applied to 185 Spanish women. The global Aiken's V of the initial instrument proposal was 0.89. The process resulted in an instrument with five factors (information, privacy, consent, support, and participation) that explained the 60% of the total variance. The score of the instrument was correlated with resilience, maternity beliefs, and positive and negative affect. External validation showed relations with age, gravida, and the number of times a woman has been in labor. Additionally, the Cronbach's α reliability was 0.93 [0.91; 0.94]. In conclusion, the instrument developed is consistent and has appropriate psychometric properties for assessing the fulfillment rights of maternity healthcare.